POSTERIOR SCLERITIS: REVIEW OF LITERATURE AND FIRST CASE REPORT FROM YEMEN - Essam Yahiya Al-shamahi; Sameha A. Al-Eryani; Emad Hassan Al-Shamahi; Nawal Mohammed Al-Hababi; Nashwan Yahya A Al-Shamahi; Hassan Abdulwahab Al-Shamahy (Universal Journal of Pharmaceutical Research, 2025)
A rare inflammatory eye illness that involves the posterior regions of the sclera. Posterior scleritis is very rare in children and more common in women. Ocular pain, headaches, and vision loss are some of its frequently vague clinical manifestations. Rheumatic conditions including systemic lupus erythematous (SLE), anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis and rheumatoid arthritis (RA) are frequently linked to the scleritis pathogenesis. A comprehensive clinical eye exam is necessary to diagnose posterior scleritis because it can mimic many other ocular disorders. Laboratory tests may reveal underlying systemic disorders, such as rheumatic disease and inflammatory markers. A precise diagnosis is aided by imaging, such as magnetic resonance imaging (MRI) and B-scan ultrasonography. Treatment includes non-steroidal anti-inflammatory drugs (NSAIDs), topical corticosteroids for moderate disease, and systemic corticosteroids for severe disease. For refractory instances, biologic therapy has grown in importance. To treat this potentially blinding condition, a multidisciplinary strategy combining rheumatology and ophthalmology is essential. This case report focuses on a 9-year-old boy who has posterior scleritis and no history of rheumatic disorders or other infections or non-infectious diseases. Peer Review History: Received 6 September 2024; Reviewed 8 November; Accepted 21 December; Available online 15 January 2025 Academic Editor: Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr Reviewers: Dr. Tamer Elhabibi, Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Dr. Taiwo O Elufioye, University of Ibadan, Nigeria, toonitaiwo@yahoo.com